2003
DOI: 10.1212/wnl.60.3.400
|View full text |Cite
|
Sign up to set email alerts
|

Early and late seizures after cryptogenic ischemic stroke in young adults

Abstract: Epilepsy is rarely a major problem in young cryptogenic ischemic stroke survivors. Early seizures are associated with stroke disability and cortical involvement. Early seizures, cortical signs, and large infarct are independent risk factors for late seizures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
194
6
27

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(255 citation statements)
references
References 41 publications
28
194
6
27
Order By: Relevance
“…The average age of vascular epilepsy occurrence established at 53 years in our study population is similar to that observed in the literature, and it reflects the age pyramid in our country. In fact, cerebrovascular injuries account for 30% to 50% of epilepsies among elderly individuals [3]. Unlike the female predominance observed in Szaflarski series [12], we recorded no such prevalence in our population.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…The average age of vascular epilepsy occurrence established at 53 years in our study population is similar to that observed in the literature, and it reflects the age pyramid in our country. In fact, cerebrovascular injuries account for 30% to 50% of epilepsies among elderly individuals [3]. Unlike the female predominance observed in Szaflarski series [12], we recorded no such prevalence in our population.…”
Section: Discussioncontrasting
confidence: 69%
“…The association of these two pathologies is not haphazard. Indeed, epilepsy is one of the most common stroke comorbidities [3]. Stroke accounts for 11% of adult symptomatic epilepsies [4], and beyond the age of 60, it is the leading cause of epilepsy (33%) ahead of degenerative diseases including Alzheimer's disease (15%), brain tumors (5%) or brain trauma injury (1% to 2%) [5].…”
Section: Introductionmentioning
confidence: 99%
“…We observed that 4.6% of our patients had an episode of seizures within 24 hours of onset of stroke. Camilo et al [10], found that the estimates of early post ischemic stroke seizures were as 2% while Lamy et al [11], observed seizures in 2.4% of 581 cryptogenic stroke patients within the first 24 hours. Dhanuka et al [9], observed that the incidence of post-stroke epilepsy in India was 13%.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of diabetes mellitus in ischemic stroke patients was observed to be having significant association with the manifestation of seizures in our study. Approximately 50% to 90% of early onset seizures appear to be simple partial seizures [2,11,13,14]. Various studies revealed simple partial seizures as the most common type (61%) in patients with early onset seizures [12,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, stroke severity was found to be a predictor of clinical poststroke seizures in some studies, [21][22][23][24] but not all. 25 Recent elec- trophysiologic studies using cEEG in patients admitted to an intensive care unit 7,8 did not find stroke severity to be a predictor of electrical epileptic seizures.…”
mentioning
confidence: 99%